2021
DOI: 10.2147/jir.s306434
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antiviral Osmotic Polymeric Film to Treat Covid-19 Early-Stage Infection

Abstract: Background: Covid-19 infection starts in the nasal cavity when viral S1 and RBD proteins bind to the host cell ACE2 receptors, the virus multiplies, causes cell lysis, and enters the circulation. This triggers a strong cytokine release and inflammation of the nasal mucosa. A multitarget approach of cleaning the nasal mucosa and suppressing chances of nasal and systemic inflammation should minimize severe respiratory consequences. Unfortunately, no such treatments are yet available. Methods: We describe the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Selection of osmotic filmogen ingredients: To find an ingredient which can be used to obtain a filmogen liquid for nasal application which is osmotic, non-cytotoxic, absorbent, and stable for 4-6h; multiple natural and synthetic ingredients were tested for osmotic and cytotoxic potential. The osmotic potential was quantified using multi-cellular live cell membrane dehydration model as described by Shrivastava et al (Ravi ) and cytotoxicity potential was measured as per the NF EN ISO 10993 (Évaluation biologique des dispositifs médicaux -Partie 5 : essais concernant la cytotoxicité in vitro n.d.) [26]. Cellular irritation potential was quantified using in vitro Bovine Corneal Opacity Test (BCOP) as described by Schrage et al [23].…”
Section: Conception Of Liquid Filmogen Glycerol Bandagementioning
confidence: 99%
See 1 more Smart Citation
“…Selection of osmotic filmogen ingredients: To find an ingredient which can be used to obtain a filmogen liquid for nasal application which is osmotic, non-cytotoxic, absorbent, and stable for 4-6h; multiple natural and synthetic ingredients were tested for osmotic and cytotoxic potential. The osmotic potential was quantified using multi-cellular live cell membrane dehydration model as described by Shrivastava et al (Ravi ) and cytotoxicity potential was measured as per the NF EN ISO 10993 (Évaluation biologique des dispositifs médicaux -Partie 5 : essais concernant la cytotoxicité in vitro n.d.) [26]. Cellular irritation potential was quantified using in vitro Bovine Corneal Opacity Test (BCOP) as described by Schrage et al [23].…”
Section: Conception Of Liquid Filmogen Glycerol Bandagementioning
confidence: 99%
“…The in vitro and in vivo cytotoxicity tests and 28-day, repeated dose, nasal application studies in rats showed no, local or systemic adverse effects. Exposing PCNS filmogen liquid on the in vitro NM mimicking multicellular live cell membrane showed that PCNS film is resistant to mechanical pressure, remains on NM for 4-6h, the osmotic activity continues during this period to attract and to trap free-floating NM contaminants towards PCNS film [26].…”
Section: Safety Stability and Osmotic Properties Of The Filmmentioning
confidence: 99%
“…An in-between strategy of treatment and protection was the one followed by Shrivastava and co-workers. In their work, they described the conception of a long-lasting (4-6 h), absorbent, osmotic, glycerol-based polymeric film using an in vitro nasal mucosa-mimicking model, containing polymers capable of not only cleaning the nasal surface, but also neutralizing pro-inflammatory cytokines and the COVID-19 S protein (Covispray) [89]. Cytokines are responsible for the activation, regulation and amplification of the immune response and their production is usually highly regulated in order to prevent systemic damage [90].…”
Section: Protectionmentioning
confidence: 99%
“…Furthermore, at 5% concentration, the final Covispray composition neutralized nearly 30% of IL-6, 80% of TNF-α and GM-CSF, as well as more than 90% of IL-10 and IL-13 (pro-inflammatory cytokines responsible for nasal and systemic inflammation). Thus, the authors considered Covispray an effective, safe and preventive treatment against multiple nasal pathologies, including COVID-19 positive symptomatic patients in early stages of the disease [89]. In Table 1, there is a summary of the different polymer-based approaches described in different studies in order to avoid viral contaminations and diseases.…”
Section: Protectionmentioning
confidence: 99%
“…The main site of Covid-19 virus mutation is S1 protein 32 The polymers incorporated in Covispray are selected to bind with whole COVID-19 S1 proteins as described in details by R Shrivastava et al 33 As viral mutations occur at the level of S1 protein, which may impact virus infectivity, antigenicity and immunogenic profile of the vaccines, 34 Covispray should be effective against all the covid-19 variants. 30 A Small Video attached with this article, explains the mode of action and the efficacy of Covispray.…”
Section: Dovepressmentioning
confidence: 99%